Animal comics : multispecies storyworlds in graphic narratives - Herman, David, 1962- (Bloomsbury Academic, 2018)
Animal characters abound in graphic narratives ranging from Krazy Kat and Maus to WE3 and Terra Formars. Exploring these and other multispecies storyworlds presented in words and images, Animal Comics draws together work in comics studies, narrative theory, and cross-disciplinary research on animal environments and human-animal relationships to shed new light on comics and graphic novels in which animal agents play a significant role. At the same time, the volume's international team of contributors show how the distinctive structures and affordances of graphic narratives foreground key questions about trans-species entanglements in a more-than-human world. The writers/artists covered in the book include: Nick Abadzis, Adolpho Avril, Jeffrey Brown, Sue Coe, Matt Dembicki, Olivier Deprez, J. J. Grandville, George Herriman, Adam Hines, William Hogarth, Grant Morrison, Osamu Tezuka, Frank Quitely, Yu Sasuga, Charles M. Schultz, Art Spiegelman, Fiona Staples, Ken'ichi Tachibana, Brian K. Vaughan, and others.